AIDS prevention practices among dental clinicians - Flores, Jocelyn Hilario
Awareness is not enough as far as danger and spread of AIDS is concerned. Health providers, educators, administrators, and researchers must internalize the etiology, mode of transmission, education and prevention of this infection.
This paper presents a study involving junior and senior clinicians of Centro Escolar University, College of Dentistry. Interviews were conducted to determine awareness about HIV/AIDS, its nature, transmission and prevention. Most of the respondents were females, single and aged 21-22. Results showed that their level of awareness is acceptable but not sufficient to help clinicians develop skills and understanding as to the risk of infection.
Keywords: AIDS (Disease).; AIDS (Disease) -- Prevention; AIDS (Disease) -- Study and teaching